Gemcitabine plus nab-paclitaxel with initial dose reduction for older patients with advanced pancreatic cancer. Issue 1 (January 2021) - Ibusuki, Mayu; Inoue, Tadahisa; Kitano, Rena; Sakamoto, Kazumasa; Kimoto, Satoshi; Kobayashi, Yuji; Ohashi, Tomohiko; Sumida, Yoshio; Nakade, Yukiomi; Ito, Kiyoaki; Yoneda, Masashi
Abstract: Objectives: For older patients with pancreatic cancer (PC), the benefits of gemcitabine plus nab-paclitaxel (GnP) are still uncertain, and the toxicity may be excessive. We aimed to examine the efficacy and safety of modified GnP (m-GnP), which is a nab-paclitaxel reduced regimen, for older patients (≥75 years) with advanced PC. Materials and Methods: In total, 34 patients met the eligibility criteria for study inclusion between 2015 and 2020. We evaluated the overall survival (OS), progression-free survival (PFS), best response, and adverse events associated with m-GnP treatment. Results: The median OS and PFS were 15.4 months and 5.9 months, respectively. The best response was partial response in 29% (10/34), stable disease in 53% (18/34), and progressive disease in 15% of patients (5/34); one patient was not evaluated. Among the grade 3 or higher hematological adverse events, neutropenia was the most frequent, occurring in 38% of patients (13/34), whereas febrile neutropenia occurred in 3% (1/34). Grade 3 or higher non-hematological adverse events occurred in 12% of patients (4/34). Early discontinuation owing to intolerable adverse events occurred in one patient, and there were no chemotherapy-related deaths. Conclusions: The present study demonstrated that m-GnP exhibited good efficacy with acceptable toxicity. To avoid early discontinuation and maintain dose intensities, initial dose reduction may be a good option for older patients with PC when receiving GnP.